INFLUENCE OF THE SIZE OF PUBLIC ACCOUNTANT FIRM, AUDITORâ€™S OPINION, PROFITABILITY, AND SOLVENCY TOWARD AUDIT DELAY IN MINING AND INFRASTRUCTURE COMPANIES LISTED IN IDX 2013-2015 - Yacherin, Faye; Astarani, Juanda (JAAKFE UNTAN (Jurnal Audit dan Akuntansi Fakultas Ekonomi Universitas Tanjungpura), 2017)
Financial statement is a tool to measure the â€œhealthâ€ of the company and timeliness in financial reporting is very important. Late reporting in financial statement have critical impact toward financial report users, as we know that that the stock market moves dynamically every minute of it, then the timeliness required in this regard. The purpose of this study is to find out whether the size of public accountant office, auditorâ€™s opinion, profitability and solvency toward audit delay. The characteristic of this study is quantitative using secondary data. Formulated by regression model the result is there is sufficient evidence that size of public accountant office, auditorâ€™s opinion and profitability have affect toward audit delay and there is no sufficient evidence that solvency have affect toward audit delay.Keyword : financial statement, audit delay, public accountant office size, auditorâ€™s opinion, profitability, solvency